TINJAUAN TENTANG PEMAHAMAN TAMU TERHADAP PEMBAYARAN DEPOSIT UNTUK TAMU YANG DATANG MELALUI PEMESANAN KAMAR SECARA ONLINE TRAVEL AGENT (OTA) DI KAWANA HOTEL PADANG - Averina Santika; Rihendra; Windy Della Sari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
Using of online travel agent (OTA) services as room reservation has often done by guests before their arrival at the hotel. After making a room reservation and the facilities desired by prospective guests, during the check-in process the guests must pay a deposit to the receptionist. Deposit is a payment of an amount of money by the guest to the Front Office Cashier as a guarantee. The application of deposits in several hotels is often done to prevent unexpected things happen. It has happened at the Kawana Padang Hotel, setting a deposit of Rp. 100,000/room. In fact, not all guests want to give their room deposit. Data collection was carried out by observing and distributing questionnaires to hotel guests as many as 100 respondents but only returned 68 questionnaires. The data can be processed with a Likert scale. The results of data processing show that the receptionist has carried out the SOP that has been determined. In handling guest deposit, there is a Front Office officer who explains in detail to the guest regarding the deposit amount, the minimum deposit amount that must be paid and always includes proof of deposit payment to the guest